The Cultural History of Moroccans in the British Gibraltar - Akfou Omar (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et des Sciences Humaines - Dhar Mahraz-, Fès, 2019)
This dissertation is presented within the context of a global debate revolving around the clash/dialogue between Islamic and Christian civilizations. The Strait of Gibraltar, for some, is the ubiquitous illustration of the dividing line between these dissimilar civilizational entities. Nevertheless, this same Strait actually illustrates, for others, the tense interactions between the two civilizations and provides evidence on the development and progress of these ties. Precisely, this dissertation addresses the question of how the various layers of Moroccan historical relations with Gibraltar (1704-1912) undermine this constructed dividing limit. These relations comprehended implementing mechanisms and policies to stop piracy in the Mediterranean and establishing administrative apparatuses to institutionalize the Anglo-Moroccan relations through launching a fix consulate in Gibraltar. Other policies were built upon dispatching diplomatic, military and educational delegations to learn the European ways in the military and civil welfare. Also, the cultural and social ties with Gibraltar grew denser after Moroccans had been allowed to settle and trade there in spite of the Spanish prohibition as the treaty of Utrecht had indicated. This window paved the way for pertinent cultural and social encounters resulting, occasionally, in Moroccans getting married to British women. Meanwhile, the Jewish community, being a minor cohort in a Muslim land, presented a significant case illustrating the internal social dynamics of Morocco, on one hand, and the external interventions on the other hand. Also, this minor community had a noteworthy cultural experience in Gibraltar. I argue that the contact zone of Gibraltar provided an early manifestation of the cultural encounters between the Moroccan Self and Christian Other that go beyond the calls for the ―inevitable‖ clash between cultures. I stress on cultural history as a tool to re-read the Anglo-Moroccan relations through shedding light on micro-histories more than macro-histories. Methodologically, this thesis moves through historical events and archives to uncover the cultural history of the encounters in Gibraltar. This is done chronologically with a focus on archival materials collected from various resources and interpretively across the readings of these archival documents.
Keywords: Moroccan Cultural Studies Center; Morocco; Gibraltar; Identity; Muslims; Jews